Learning outcomes with visual thinking strategies in nursing education. (April 2017) - Moorman, Margaret; Hensel, Desiree; Decker, Kim A.; Busby, Katie
Abstract: Background: There is a need to develop innovative strategies that cultivate broad cognitive, intrapersonal, and interpersonal skills in nursing curricula. The purpose of this project was to explore transferable skills students gained from Visual Thinking Strategies (VTS). Method: This qualitative descriptive study was conducted with 55 baccalaureate nursing students enrolled in an entry level healthy population course. The students participated in a 1 h VTS session led by a trained facilitator. Data came from the group's written responses to a question about how they would use skills learned from VTS in caring for patients and in their nursing practice. Results: Content analysis showed students perceived gaining observational, cognitive, interpersonal, and intrapersonal skills from the VTS session. Conclusions: VTS is a unique teaching strategy that holds the potential to help nursing students develop a broad range of skills. Studies are needed on optimal exposure needed to develop observational, communication, collaboration, and critical thinking skills. Research is also needed on how skills gained in VTS translate to practice. Highlights: Visual Thinking Strategies (VTS) can help nursing students learn collaboration and teamwork. Students perceive that VTS can help them to interpret patient conditions and observational skills better. Students perceive that VTS can improve communication and active listening.